Tricuspid Valve Replacement on Beating Heart with a Bioprosthetic Valve: A case report (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 59-61 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13563